Grain refinement, twin formation and mechanical properties of magnesium welds with addition of CNTs and TiC particles - Yongkang Gao; Lianyong Xu; Kangda Hao; Yongdian Han; Lei Zhao; Wenjing Ren (Journal of Magnesium and Alloys, 2025)
In this work, microstructure and mechanical properties of Mg weld with addition of carbon nanotubes (CNTs) and TiC particles were investigated. The results showed that the weld microstructure was mainly presented as equiaxed grains with almost high angle grain boundaries. The introduction of reinforcements promoted the formation of precipitates and refined the grains effectively, the average grain size was refined by 51% and 23% with addition of CNTs and TiC particles, respectively. The dislocation density and the fraction of CSL boundaries were increased with addition of CNTs, while those were decreased with addition of TiC particles. Besides, the infrequent {101¯3} contraction twins formed within the weld due to the stress concentration caused by dislocation accumulation, which contributed to the Σ29 CSL boundary. The ultimate tensile strength and elongation rate were increased by 13.5% and 40% with addition of CNTs, while the ultimate tensile strength and micro-hardness were increased by 14.8% and 20.9% with addition of TiC particles.